2012
DOI: 10.1001/archsurg.2012.751
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Evaluation of Alternative Sites for Needle Decompression of Tension Pneumothorax

Abstract: To compare the distance to be traversed during needle thoracostomy decompression performed at the second intercostal space (ICS) in the midclavicular line (MCL) with the fifth ICS in the anterior axillary line (AAL). Design: Patients were separated into body mass index (BMI) quartiles, with BMI calculated as weight in kilograms divided by height in meters squared. From each BMI quartile, 30 patients were randomly chosen for inclusion in the study on the basis of a priori power analysis (n=120). Chest wall thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 16 publications
3
47
1
1
Order By: Relevance
“…However, depending on the needle or cannula used, this is often ineffective at relieving the tension, as the needle may not be long enough to reach the pleural space, and it may dislodge or kink, rendering it useless, potentially allowing the tension pneumothorax to recur. 16,17 Thoracostomy is therefore recommended over needle decompression. [18][19][20] Thoracostomy is achieved by making a skin incision followed by blunt dissection with forceps or finger through the intercostal muscles and pleura in the same location that an intercostal drain is usually placed (fourth or fifth intercostal space, in the mid-axillary line).…”
Section: Management Of Reversible Causesmentioning
confidence: 99%
“…However, depending on the needle or cannula used, this is often ineffective at relieving the tension, as the needle may not be long enough to reach the pleural space, and it may dislodge or kink, rendering it useless, potentially allowing the tension pneumothorax to recur. 16,17 Thoracostomy is therefore recommended over needle decompression. [18][19][20] Thoracostomy is achieved by making a skin incision followed by blunt dissection with forceps or finger through the intercostal muscles and pleura in the same location that an intercostal drain is usually placed (fourth or fifth intercostal space, in the mid-axillary line).…”
Section: Management Of Reversible Causesmentioning
confidence: 99%
“…This clinical success rate seems exceptionally high considering evidence suggesting that NT may fail to decompress TPTX in up to 50% of patients. [9][10][11][12]27 Furthermore, because a similar rate of clinical improvement was reported in patients surviving their injuries as in patients who did not survive, it seems that these high success rates are the result of inaccurate subjective assessment. In the present study, 32% of patients undergoing NT eventually had a CD installed in the prehospital setting, implying a true failure rate more consistent with that reported in the available literature.…”
Section: Discussionmentioning
confidence: 85%
“…[10][11][12] In other reports, techniques such as cadaver dissection 13,14 and ultrasonography 15,16 were used to detect the penetration of catheters. On the basis of these findings, a recommendation for change was issued, and many prehospital organizations have adopted the use of longer catheters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cadaver [47], animal [48][49][50], and clinical [51][52][53][54] studies have suggested that use of a small (3.2 cm) needle in the standard site (second intercostal space, midclavicular line) is not reliable, likely due to the thickness of the chest wall at this site and the small size of the needle or catheter. Even when proper placement is confirmed laparoscopically in animal models, Martin and colleagues showed that a 14-gauge angiocatheter fails to relieve tension physiology 64 % of the time [48].…”
Section: Tension Pneumothoraxmentioning
confidence: 99%